Culture-specific Investment Attractiveness Index: An Original Composite Indicator - Tocar, Sebastian (International Journal of Economics and Financial Issues, 2019)
This paper presents an original approach to the investment attractiveness of the countries. The author developed an index of investment attractiveness which takes into account indicators of cultural specificity. The specialty literature offers a variety approaches in which different factors that are considered determinants of foreign direct investment (FDI) are analyzed. However, even if cultural are frequently mentioned (and sometimes analyzed), they rarely represent an object of the research of FDI determinants. As for the indexes of investment attractiveness identified in the literature, the situation is even more difficult, and the cultural factors seem to be avoided. The elaboration of the Culture-specific Investment Attractiveness Index through the application of the Principal Component Analysis technique proved to be efficient, the new construct being reliable. Further analysis of the connection between the Index and the volume of FDI attracted confirm its suitability for explaining the localization of FDI in Europe. Keywords: Investment Attractiveness Index, FDI, culture JEL Classifications: C38, C43, F21, Z19 DOI: https://doi.org/10.32479/ijefi.8293